Performance of Sweet Potato (Ipomoea batatas L.) Cultivars in Different Seasons in Assam - Deka, K. K; Borah, P; Das, M. R; Borgohain, S (JOURNAL OF ROOT CROPS, 2014)
Seven sweet potato cultivars were evaluated at Horticultural Research Station, Kahikuchi, Assam, during 2008 and 2009, both in kharif and rabi seasons under rainfed conditions. The shoot growth, tuber yield and tuber quality parameters were evaluated in both the seasons. The growth parameters viz., vine length, branch numbers and petiole length were greater in kharif as compared to rabi season, whereas tuber yield was greater in rabi season than kharif in all the cultivars. The cultivar Kothal Kuhia (local) exhibited better growth performance in both the seasons and produced the maximum tuber yield (26.17 t ha -1) during the rabi season than in kharif. The tuber yield of HRS-1(24.91 t ha -1) and 440074 (24.09 t ha-1) were on par with Kothal Kuhia. The starch content of tubers of all the sweet potato cultivars tested was also found to be greater in rabi than in kharif season. Starch content of fresh tubers was maximum in Kothal Kuhia during rabi season (24.99%), whereas, it was minimum in IB-97-615 (18.24%). The cultivars Kothal Kuhia and 440047 proved to be superior with respect to growth, yield and starch content of tuber in both kharif and rabi seasons. Both these cultivars can be recommended for cultivation under the agro-climatic conditions of Assam.